2016
DOI: 10.21548/37-2-827
|View full text |Cite
|
Sign up to set email alerts
|

Malolactic Fermentation Induced by Lactobacillus plantarum in Malbec Wines from Argentina

Abstract: The current market requirements to obtain wines with enhanced complexity and varietal character propose the finding of new microorganisms capable of driving the malolactic fermentation (MLF) and contributing to new and distinctive sensory profiles in wines. During MLF, malic acid naturally present in the must is converted into lactic acid by a decarboxylation reaction driven by lactic acid bacteria. Recently, a new strain of Lactobacillus plantarum suitable for MLF in high-pH wines was selected. This study eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The induction of malolactic fermentation is beneficial to some wines, but in white wines, such as Chenin blanc, it may result in the production of off-flavours such as diacetyl (Bartowsky & Henschke, 2004). Nevertheless, the use of alternative technologies to develop malolactic fermentation in wine is now a priority (Maicas, 2001;Betteridge et al, 2015;Lerena et al, 2016;Lucio et al, 2017).…”
Section: Malic Acidmentioning
confidence: 99%
“…The induction of malolactic fermentation is beneficial to some wines, but in white wines, such as Chenin blanc, it may result in the production of off-flavours such as diacetyl (Bartowsky & Henschke, 2004). Nevertheless, the use of alternative technologies to develop malolactic fermentation in wine is now a priority (Maicas, 2001;Betteridge et al, 2015;Lerena et al, 2016;Lucio et al, 2017).…”
Section: Malic Acidmentioning
confidence: 99%
“…The 85 physiological effect of pH on LAB is also well defined. RNA sequencing revealed the 86 differential expression of several genes related to the metabolism of amino acids, 87 carbohydrates, membrane transport and energy metabolism as part of the genetic 88 response of O. oeni strain SD-2a to low pH ( to complete MLF at the laboratory and semi-industrial scale revealed that bacterial survival was related more to pH evolution during MLF, than the initial pH of the must 97 (Lerena et al 2016). In all cases the musts showed initial pH values over 3.6 but the 98 pH showed dynamic behaviour, changing as MLF progressed.…”
Section: Introduction 31mentioning
confidence: 99%
“…The L. plantarum 1UHCC bacteria are able to metabolize these organic acids. Organic acids can then be utilized by L. plantarum as a carbon source (Filannino et al, 2014;Lerena et al, 2016). Research has been reported by Ge et al, (2019), that L.plantarum 1UHCC bacteria can inhibit protein oxidation during the process of fermentation on processed meat (sausage), increase protein degradation and provide comparative antioxidant effects as strains for commercial purposes.…”
Section: Ph Valuementioning
confidence: 99%